The Role of Entrepreneur Knowledge and Self-Efficacy toward Technopreneurship: The Moderating Effect of Learning Strategies - Adriani, Deni; Ahman, Eeng; Mulyadi, Hari; Nuryanti, B Lena (Jurnal Pendidikan Progresif, 2024)
The Role of Entrepreneur Knowledge and Self-Efficacy toward Technopreneurship: The Moderating Effect of Learning Strategies. Objective: To determine the effect of entrepreneur knowledge and self-efficacy on technopreneurship which is moderated by the learning strategy of Universitas Negeri Medan students. Method: This research was done using a quantitative approach with a survey method. The study population was students of the faculty of economics, the sample tehnique was random sampling and the number of selected samples was 198 respondents. Questionnaires were used to collect data from research participants for 15 days. The data were analyzed using moderate regression analysis (MRA) using SPSS. Findings: entrepreneur knowledge has a positive and significant effect on technopreneurship, self-efficacy has a positive and significant effect on technopreneurship. Learning strategy moderate the influence of entreprenur knowledge on tecunopreurship  Furthermore, the learning strategy also moderates the effect of self-efficacy on technopreneurship. Conclusion:These findings imply that university managers, faculty, and entrepreneurship centers to review the intensity of technopreneurial activities so that students can benefit from these programs. Focusing more on direct experience rather than theory or classroom lectures will help students to understand more about technoprenership and thus choose technopreneurship as their career. Keywords: entrepreneur knowledge, self-efficacy, technopreneurship, learning strategies.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202457